2007
DOI: 10.1007/bf02893442
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of hyperuricemia with rasburicase in children with leukemia and non-Hodgkin’s lymphoma

Abstract: To prevent acute renal failure in children at risk for developing tumor lysis syndrome due to acute lymphoblastic leukemia or non-Hodgkin's lymphoma treated according to international BFM protocols, we investigated recombinant urate oxidase (rasburicase) in the first Central European openlabeled, prospective, multicenter phase IV trial. Rasburicase was administered intravenously, at 0.2 mg/kg for 5 consecutive days to 36 patients. Blood levels of uric acid, creatinine, phosphorus, calcium, lactate dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…The study reported that the duration of rasburicase treatment should be tailored to the duration and intensity of tumor cell lysis in the patient by closely monitoring clinical chemistry. The superiority of rasburicase in comparison with allopurinol for the prophylaxis and treatment of hyperuricemia in children with leukemia and lymphoma has been demonstrated [24]. Rasburicase, administered at a dose of 0.20 mg/kg for 5 consecutive days, resulted in a rapid and significant decrease in uric acid levels after 4 h [24], in line with the findings reported in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study reported that the duration of rasburicase treatment should be tailored to the duration and intensity of tumor cell lysis in the patient by closely monitoring clinical chemistry. The superiority of rasburicase in comparison with allopurinol for the prophylaxis and treatment of hyperuricemia in children with leukemia and lymphoma has been demonstrated [24]. Rasburicase, administered at a dose of 0.20 mg/kg for 5 consecutive days, resulted in a rapid and significant decrease in uric acid levels after 4 h [24], in line with the findings reported in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…The superiority of rasburicase in comparison with allopurinol for the prophylaxis and treatment of hyperuricemia in children with leukemia and lymphoma has been demonstrated [24]. Rasburicase, administered at a dose of 0.20 mg/kg for 5 consecutive days, resulted in a rapid and significant decrease in uric acid levels after 4 h [24], in line with the findings reported in the current study. Rasburicase was also a more potent and more rapid uricolytic agent than allopurinol.…”
Section: Discussionsupporting
confidence: 91%
“…4 Recombinant urate oxidase (rasburicase) has been found to be useful in managing hyperuricemia. [5][6][7][8] The recommended pediatric dose of rasburicase (0.15-0.20 mg/kg for 3-7 days) is very effective for adults as well. Indeed, it usually lowers the serum uric acid concentration to levels much below the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic treatment of TLS is aggressive hydration and allopurinol before cytotoxic therapy. The efficacy of rasburicase is considered superior to that of allopurinol even for prophylaxis [5]. Sunitinib is an oral antityrosine kinase inhibitor that has antiangiogenic and antitumor activities.…”
Section: Discussionmentioning
confidence: 99%